2019
DOI: 10.1111/ecog.04690
|View full text |Cite
|
Sign up to set email alerts
|

Fish assemblage convergence along stream environmental gradients: an intercontinental analysis

Abstract: Species that pass through similar environmental filters, regardless of geographic proximity or evolutionary history, are expected to share many traits, resulting in similar assemblage trait distributions. Convergence of assemblage trait distributions among different biotic regions would indicate that consistent ecological processes produce repeated patterns of adaptive evolution. This study analyzes trait–environment relationships across multiple stream fish assemblages representing evolutionarily divergent fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 59 publications
2
39
0
Order By: Relevance
“…In stream fishes, functional diversity metrics were related to water depth, substrate complexity, and water velocity in a manner consistent with the stress‐dominance hypothesis. This pattern was fairly congruent across regions (Table ; Bower & Winemiller, ). FRic was inversely associated with water velocity, suggesting that requirements for coping with hydraulic drag restrict assemblage trait space in stream microhabitats with fast flows.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In stream fishes, functional diversity metrics were related to water depth, substrate complexity, and water velocity in a manner consistent with the stress‐dominance hypothesis. This pattern was fairly congruent across regions (Table ; Bower & Winemiller, ). FRic was inversely associated with water velocity, suggesting that requirements for coping with hydraulic drag restrict assemblage trait space in stream microhabitats with fast flows.…”
Section: Discussionmentioning
confidence: 69%
“…In stream fishes, functional diversity metrics were related to water depth, substrate complexity, and water velocity in a manner consistent with the stress-dominance hypothesis. This pattern was fairly congruent across regions (Table S5; Bower & Winemiller, 2019).…”
Section: Functional Diversity Along Environmental Gradientsmentioning
confidence: 60%
See 2 more Smart Citations
“…Local scale variables, like water velocity and habitat structural complexity, have been reported to function as universal environmental filters, producing similar assemblage trait distributions in streams across different regions (Bower & Winemiller, 2019). Studies conducted on a wider spatial scale found instead a greater effect of landscape variables over local ones (Esselman & Allan, 2010).…”
Section: Discussionmentioning
confidence: 99%